Digital Branding Enhancement of Sambas Liberica Coffee Potention with SWOT Analysis in Data Identification - Prihartini, Narti; Firdania, Milda Surgani; Akbari, Fiqih (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2026)
The development of local commodities, such as Sambas Liberica coffee, requires a comprehensive strategic analysis to identify internal and external factors influencing its growth. Early analysis identified that to support this development need the work from stakeholders such government in supporting MSMEs of Sambas Liberica Coffee for marketing and business assistance. The academic institution through the initiation of teaching factory can provide the valuable researchs that could also support potention of Liberica Coffee in Sambas Regency. This research employs a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to map these factors, which are then quantitatively evaluated using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. The study highlights the pivotal role of Sambas State Polytechnic (Poltesa) through its Liberica Research Center, which provides academic strength, digital technology application, and collaborative synergy with local farmers and MSMEs. The research specifically examines the implementation of digital branding strategies through Instagram @plrcpoltesa as a hands-on technology approach to support market expansion. The IFE matrix score of 2.95 indicates a strong internal position, driven by unique product attributes and strong academic support. Meanwhile, the EFE matrix score of 2.65 shows a responsive capacity to external opportunities, particularly the global specialty coffee trend and digital market expansion. The strategic recommendations emphasize leveraging digital platforms for brand positioning and market penetration.